COMPARISON OF AMIODARONE VERSUS MAGNESIUM SULPHATE IN PREVENTION OF POST OPERATIVE ARRHYTHMIAS IN OPEN HEART SURGERY: A RANDOMIZED CONTROLLED TRIAL AT LADY READING HOSPITAL PESHAWAR - Amjid Ali,; Muhammad Haseeb Moin Ud Din Baloch,; Sayed Shah Hassanain,; Muhammad Izaz,; Muhammad Aftab Ahmad, (Journal of Postgraduate Medical Institute, 2023)
Objective: To compare the frequency of postoperative arrhythmias with amiodarone versus magnesium sulphate in patients undergoing open heart surgery Methodology: This randomized Controlled trial was done at Department of Anethesia Lady Reading Hospital, Peshawar. Eighty patients of age 40-70 years, either gender undergoing open heart surgery under general anesthesia were enrolled via Non-probability, consecutive sampling technique. Then they were divided in two groups by using lottery method. In group A, patients were given loading dose of amiodarone 5mg/Kg and in group B, patients were given 2g of MgSO4 in 100ml of isotonic 0.9% solution intravenously. After surgery, patients were followed-up there for 3 days. Patients were monitored through ECG monitor for postoperative arrhythmias. Results: The mean age of patients was 49.93±7.38 years in amiodarone group while 51.45±7.31yeas in MgSO4 group. There were 26 (65%) males and 14 (35%) females in group A while 15 males (37.5%) and 25 females (62.5%) in group B. Postoperative arrhythmias were observed in 10 (25%) cases with amiodarone while in 16 (40%) cases with MgSO4, although the difference was insignificant (p>0.05). Conclusion: The frequency of postoperative arrhythmias is reduced with using amiodarone than MgSO4.